Effects of Access Database Management System Hands-on Experience on Students’ Academic Achievement and SelfEfficacy in Database Management - Joseph. C. (PhD), Onuoha; Michael I, Onyepunuka; Orie (PhD), Idika Ezinne; Fumnanya, Ekwesaranna; Chukwuma (PhD), Emmanuel (International Journal of Psychosocial Rehabilitation, 2021)
The purpose of this study is to determine the effect of access database management system’s hands-on experience on students’ achievement, interest and self-efficacy in database management in economics education. Quasi-experimental design specifying pre-test post-test control group design was adopted. The sample size was 72 students from two purposively selected intact classes. Simple random sampling technique was used to assign the classes, one to control group and the other to the experimental group. Three research questions and two null hypotheses were formulated to guide the study. Validated and trial-tested Databank Management Achievement Test (DMAT) was used for data collection for both the pretest and posttest while Validated Databank Management Interest Inventory (DMII) and Databank Management Self Efficacy Scale (DMSS) were used to collect data on students’ interest in Databank Management and students’ self-efficacy belief in Databank Management respectively. Mean and standard deviation were used to answer research questions and analysis of covariance used to test the null hypothesis at 0.05 probability level. The result proved that Access Hands-on Experience approach is more efficacious in enhancing students’ achievement, interest and self-efficacy believe in Databank Management than the lecture method. It was recommended that Hands-on Experience should be encouraged in teaching Databank Management in tertiary institutions and that its use should be popularized through workshops, seminars and conferences